EFIKASI DIRI KADER ANTI PENYALAHGUNAAN NARKOBA BERBASIS PELAJAR DI SMA SURABAYA - Rima Diana Nurrilla (Jurnal Ilmu Kesehatan Masyarakat, 2018)
Drug abuse has increased each year and and has spread to adolescents who are still in school. Goverments city of Surabaya issued preventive drug abuse policies (Perwali) Number 65 of 2014about policies and strategies for the area in the field of prevention, combating drug abuse and illict drugs (P4GN). One of the priority programs of the Government of the city of Surabaya is forming student-based cadre. The formation of drug abused student-based cadre is a form of social reinforcement among students. The purpose of the research is to find out academic self efficacy of drug abused student-based cadre in Surabaya High School. This research is descriptive research with using qualitative approach. The results showed that self efficacy of drug abused student-based cadre can be seen through the dimension level, the dimension of generality, and dimensions of strenght. Dimension level faced cadres was considered patronizing by friends, many of friends are less open regarding their problems , and the issue abaout time management.The dimension of generality is obtained because the respondents consider they are able to carry out his duties as motivate friends, discussions, sharing drug-related information to a friend, an extension of the hand counselor teacher and positive activities that lead to prevention drugs. The dimensions of the strenght that is owned by the respondent based on some of the things that is add to the experience and insights, like to help friends, fighting drugs and because chosen to represent the school.